Prevention and Management of Frailty - Byeon, Haewon; Nah, Jaewon (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
It is important to prevent and manage the frailty of the elderly because their muscle strength and physical activity decrease in old age, making them prone to falling, depression, and social isolation. In the end, they need to be admitted to a hospital or a nursing home. When successful aging fails and motor ability declines due to illness, malnutrition, or reduced activity, frailty eventually occurs. Once frailty occurs, people with frailty do not have the power to exercise or the power to move. The functions of the heart and muscles are deteriorated more rapidly when they are not used. Consequently, frailty goes through a vicious cycle. As one's physical fitness is deteriorated, the person has less power to exercise, poorer cognitive functions, and inferior nutrition intake. Consequently, the whole body of the person deteriorates. Therefore, in addition to observational studies to identify risk factors for preventing aging, various intervention studies have been conducted to develop exercise programs and apply them to communities, hospitals, and nursing homes for helping the elderly maintain healthy lives. Until now, most aging studies have focused on physical frailty. However, social frailty and cognitive frailty affect senile health negatively just as much as physical frailty. Nevertheless, little is known about social frailty and cognitive frailty. This special issue includes original experimental studies, reviews, systematic reviews, and meta-analysis studies on the prevention of senescence (physical senescence, cognitive senescence, social senescence), high-risk group detection, differentiation, and intervention.